Information Systems Security 5th International Conference, ICISS 2009 Kolkata, India, December 14-18, 2009 Proceedings - Prakash, Atul.; Sen Gupta, Indranil. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the 5th International Conference on Information Systems Security, ICISS 2009, held in Kolkata, India, in December 2009. The 17 revised full papers and 4 short papers, presented together with 4 keynote talks were carefully reviewed and selected from 85 initial submissions. The papers are organized in topical sections on authentication, verification, systems security, behavior analysis, database security, and cryptography.